Genomological Virus VS Computer Virus (British Journal of Multidisciplinary and Advanced Studies, 2023)
A genomological virus is a genomic-thing that possesses Genome which is an automatic molecular machine capable of self-replicating and synthesizing all individuals of its species using its nutritive substances as raw materials in its compatible environment whereas a computer virus is a nongenomic-thing being a man-made (written) malicious program. In computing, a program also known as application or software, is a set of instructions that processes input, manipulate data and outputs a result. The key objective of this study is to demonstrate that the genomological & computer viruses are totally unrelated and their analogic similarities are only metaphoric. The contents of Figures & Table 1 are designed to serve as Results in the targetful strategy of this study. Genomological viruses & computer viruses are not related homologically, genomically or evolutionally. The term replication (a type of reproduction in Microgenomology) is not appropriate to use for computer viruses as it is used only in microgenomology and molecular genomology. Cyber security can be 100% efficient if and only if attacks by black hat hackers & unethical grey hat hackers are prevented 100%.